If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 = a + -25 Reorder the terms: 56 = -25 + a Solving 56 = -25 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 56 + -1a = -25 + a + -1a Combine like terms: a + -1a = 0 56 + -1a = -25 + 0 56 + -1a = -25 Add '-56' to each side of the equation. 56 + -56 + -1a = -25 + -56 Combine like terms: 56 + -56 = 0 0 + -1a = -25 + -56 -1a = -25 + -56 Combine like terms: -25 + -56 = -81 -1a = -81 Divide each side by '-1'. a = 81 Simplifying a = 81
| 6(3x+4)=5*14 | | -6ba^2(2b^2-3b+16)= | | 6(3x+4)=5(14) | | 5.1x=8.8 | | -14x-4=14x+7+8 | | 7-3[5-(2+5)]= | | 4(2p+3)=5p+24 | | (x+9)6=(x+4)5 | | 84=6x+3(2x-12) | | -.10(7)+.35x=.05(x-2) | | 24.8=a-38.4 | | x^2-3x+2.25= | | (x+3)9=(4x+7)2 | | 5-x/x+4=0 | | 64x^2-25x=0 | | x+10=26 | | 6(x-5)+5x=14 | | 4x^4-2x^2+1=0 | | -.01x^2+.8x+6.2=0 | | 28x-13-16x=3(4x-5)+2 | | x+1(7)=(6x+5)1 | | 0.29x-0.25=0.43x+0.03 | | x(8)-5(8)=3x | | 6x-5(-x+13)=-197 | | -2(4x-5)=-3 | | 5-2x=3(7-2x) | | 3(-2-3x)=-7x-4 | | 10x+6Y=180 | | 4x^2+x+10=0 | | 4x-20=3x+7 | | 6(5x-3)+9=30x-9 | | 5(x-2)-1=2x+3(-3+x) |